2018
DOI: 10.32674/jis.v8i1.153
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and Leveraging Chinese International Students’ Strengths for Success

Abstract: This study used an Appreciative Education framework to explore the strengths of Chinese international students and to identify areas where support is needed during their transition to U.S. higher education settings. Using a convergent mixed methods design with data collected from surveys, interviews and focus groups, the complex nature of the transition process was explored. While commitment and motivation, as well as familial support, were identified as strengths based on survey data, interview and focus grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This finding highlights the importance of providing formalized writing instruction and support to international students who are still acquiring a new language, learning to write academically, and only starting to socialize into their disciplinary discourse. Apart from the support from an ESL program, faculty teaching content courses could make academic content comprehensible through sheltered instruction techniques, which are commonly used in the K-12 setting in the mainstream classes including English language learners (Echevarria, Vogt, & Short, 2016;He & Hutson, 2018). Taking challenges faced by international students into consideration, they could also present their expectations and grading rubrics more explicitly to international students.…”
Section: Discussionmentioning
confidence: 99%
“…This finding highlights the importance of providing formalized writing instruction and support to international students who are still acquiring a new language, learning to write academically, and only starting to socialize into their disciplinary discourse. Apart from the support from an ESL program, faculty teaching content courses could make academic content comprehensible through sheltered instruction techniques, which are commonly used in the K-12 setting in the mainstream classes including English language learners (Echevarria, Vogt, & Short, 2016;He & Hutson, 2018). Taking challenges faced by international students into consideration, they could also present their expectations and grading rubrics more explicitly to international students.…”
Section: Discussionmentioning
confidence: 99%
“…Also, equipped with better knowledge, they can improve their economic standing in society. For students seeking knowledge, they need to have an open mind to listen to other people's ideas and views and be receptive to criticisms of their supervisors, lecturers, and colleagues (He & Hutson, 2018). However, it is common knowledge that some students will be reluctant to admit their weaknesses, which may be due to their egoistic or negative attitudes.…”
Section: Study Commitmentmentioning
confidence: 99%
“…Conversely, they found that a lack of parental feedback and lack of caring significantly contribute to academic amotivation among students. He and Hutson (2018) used an appreciative education framework to evaluate the strengths of Chinese international students and the potential for support during their academic transition. From surveys, interviews, and focus groups, the authors found that an obligation to family support from home as well as motivation and commitment to success are positively related to acculturation success.…”
Section: Creating Clear Connections Between Traditional Measures Of Amentioning
confidence: 99%